The effectiveness of smart healthcare for patients with rheumatoid arthritis: A systematic review and meta-analysis - Yin Yu; Meijiao Wang; Hejing Pan; Lin Huang; Haichang Li; Xuanlin Li (PLoS ONE, 2026)
Objectives This study aimed to evaluate the impact of smart healthcare interventions on disease activity, self-efficacy, self-management, functional levels, and quality of life in rheumatoid arthritis (RA) patients, as well as any associated adverse events. Method A systematic search was conducted in PubMed, EMBASE, and Cochrane Library for randomized controlled trials (RCTs) from inception to August 2024, using relevant medical subject headings and keywords. The Cochrane risk of bias tool was employed to assess bias risk. A random effects model was used, calculating the standardized mean difference (SMD) and 95% confidence intervals (CIs). Heterogeneity was assessed with Chi-square and I 2 tests. Result This meta-analysis included 18 RCTs published between 2015 and 2024, with follow-up periods ranging from 3 months to 1 year. Results revealed a significant reduction in Disease Activity Score 28 (DAS28) in the smart healthcare intervention group compared to controls [SMD 95% CI: −0.22 (−0.38, −0.05), I 2 = 28.8%, P = 0.011]. Additionally, quality of life showed significant improvement as measured by EQ-5D scores [SMD 95% CI: 0.16 (0.01, 0.32), I 2 = 0.0%, P = 0.033]. Significant improvement was also observed in functional capacity [SMD 95% CI: −0.30 (−0.54, −0.06), I 2 = 0.0%, P = 0.014]. However, no statistically significant effects were found for self-efficacy [SMD 95% CI: 0.12 (−0.12, 0.35), I 2 = 0.0%, P = 0.340], self-management ability [SMD 95% CI: 0.11 (−0.17, 0.39), I 2 = 0.0%, P = 0.451], or RA knowledge [SMD 95% CI: 0.46 (−0.14, 1.07), I 2 = 75.98%, P = 0.133]. Conclusion Smart healthcare interventions show promise in reducing disease activity and improving physical function and quality of life in patients with rheumatoid arthritis. While these findings support the potential value of digital health solutions in RA management, further validation through more rigorous methodological designs is needed to confirm long-term effectiveness and clinical utility.